α2β1 integrins spatially restrict Cdc42 activity to stabilise adherens junctions - Jake D. Howden; Magdalene Michael; Willow Hight-Warburton; Maddy Parsons (BMC Biology, 2021)
Abstract Background Keratinocytes form the main protective barrier in the skin to separate the underlying tissue from the external environment. In order to maintain this barrier, keratinocytes form robust junctions between neighbouring cells as well as with the underlying extracellular matrix. Cell–cell adhesions are mediated primarily through cadherin receptors, whereas the integrin family of transmembrane receptors is predominantly associated with assembly of matrix adhesions. Integrins have been shown to also localise to cell–cell adhesions, but their role at these sites remains unclear. Results Here we show that α2β1 integrins are enriched at mature keratinocyte cell–cell adhesions, where they play a crucial role in organising cytoskeletal networks to stabilize adherens junctions. Loss of α2β1 integrin has significant functional phenotypes associated with cell–cell adhesion destabilisation, including increased proliferation, reduced migration and impaired barrier function. Mechanistically, we show that α2β1 integrins suppress activity of Src and Shp2 at cell–cell adhesions leading to enhanced Cdc42–GDI interactions and stabilisation of junctions between neighbouring epithelial cells. Conclusion Our data reveals a new role for α2β1 integrins in controlling integrity of epithelial cell–cell adhesions.